The impact of maillard crosslinking on soy proteins and tofu texture - Suhaimi Md. Yasir; K. H. Sutton; M. P. Newberry; N. R. Andrews; J. A. Gerrard (2014)
In this paper, we explore the use of Maillard cross-linking agents (formaldehyde, glyceraldehyde and glutaraldehyde) in tofu, to probe the relationship between cross-linking of soy proteins and tofu texture. 1–2 mM glutaraldehyde treatment resulted in an acceptable product with altered microstructure. At 2 mM glutaraldehyde, the fracture force was increased if the reagent was added before soymilk boiling, but decreased if it was added after boiling, when more cross-linking was observed due to the denaturation of the proteins. The fracture forces and microstructures are hard to rationalise in terms of cross-linking, suggesting that other factors, such as non-cross-linking protein glycation, may be responsible for the observed changes. Taken together with the results reported in the previous paper, these findings suggest that protein cross-linking agents may change the functional properties of tofu via non-cross-linking modifications of the sidechains of the amino acid residues, changing their isoelectric point and their gelation properties.